Sustainable development governance in environmental impact assessment practice. - Ismail, Amina Omar (My University, 2016)
A qualitative study was conducted to explore natural scientist Environmental Assessment Practitioners’ current knowledge of sustainable development governance, in order to understand their potential to be agents of social learning to effect paradigmatic change in Environmental Impact Assessment (EIA) practice. Data was collected from recently graduated and senior practitioners in a single environmental consultancy as a case study. The consultancy based in Johannesburg, South Africa, was well established and provided the practitioners with many opportunities to improve their EIA knowledge for application in practice. Practitioners, for example could access training opportunities and participate in EIA and environmental governance discipline groups established at the practice. The case study focused on a specific work environment to ascertain if common work experiences influenced the construction of knowledge. The study used the theories of reasoned action and planned action as a framework to structure the data for exploring the study subjects’ knowledge of sustainable development governance and its relationship with factors contributing to their understanding of the term. The study found that the practitioners did not have sufficient knowledge of sustainable development governance to enable them to engage in “triple loop learning”. This type of social learning questions both the values and its underlying paradigms in an institution (Pahl-Wostl, 2009). Practitioners were therefore unable to shift the EIA mechanism from its rationalist planning paradigm towards the adoption of the principles of sustainable development governance worldview. Two main factors were found to contribute towards practitioners’ current understanding of sustainable development governance. The first was a structural constraint in the academic education system that required natural science undergraduates to pursue only natural science courses. The second was a subjective norm established at work that expressed governance as compliance with legislation, international standards and norms, and with corporate policies. A secondary factor of personal motivation was also identified which may have added a low level of subjectivity in the knowledge of a few practitioners. 2 Findings from this study may be useful when considering interventions directed towards improving knowledge for progressing sustainable development governance in EIA practice.
MM
Keywords: Environmental impact analysis -- South Africa. Sustainable development -- South Africa.